(untitled) (Innovative professional education, 2025)
The main task of higher education is to create conditions for the personal and professional development of future specialists, their further growth in professional activities, which makes it possible to find and implement the most effective, socially acceptable strategies for professional careers. The traditional system of vocational education does not take into account the specifics of the professional formation of such specialists, in particular, the formation of special professionally significant qualities for designing a career path